(untitled) (Research, Society and Development, 2021)
Objective: to analyze the factors associated with mortality up to 28 days in premature infants with very low birth weight (<1500 g). Methods:Retrospective cohort study with a quantitative nature, and data from medical records of children born from July 31, 2015 to August 1, 2016 were collected, based on the delivery records in the delivery room and summary of hospitalization in Neonatal ICU of a public maternity hospital in Maranhão. The variables studied were: maternal characteristics, characteristics of the newborn at birth and neonatal evolution, associated with mortality up to 28 days. The variables associated with death were determined by logistic regression, estimating the odds ratios with 95% CI. Results: Of the 209 newborns studied, 87 (41.6%) died. They showed a significant association with death: gestational age less than 28 weeks (OR = 4.99; CI = 95%: 2.02-12.32), birth weight less than 1000 g (OR = 4.34; CI = 95%: 1.87-10.04), APGAR in the 5 ’less than 7 (OR = 4.44; CI = 95%: 1.46-13.48), use of surfactant (OR = 3.72 ; 95% CI: 1.64-8.43) and who had pulmonary hemorrhage (OR = 19.17; CI = 95%: 4.46-82.42). Maternal characteristics did not remain in the final model, which suggests that the death that occurred in the neonatal period is influenced by characteristics of the newborn and by care factors. Conclusion: The causes of death in the neonatal period were associated with lower gestational age, lower birth weight, low vitality at birth, as well as the use of surfactant and the presence of pulmonary hemorrhage. There is a need to identify and establish practices to improve care for pregnancy, childbirth, and the newborn.